West Nile Virus Seroprevalence Among Outdoor Workers in Southern Italy: Unveiling Occupational Risks and Public Health Implications - Angela Stufano; Valentina Schino; Gabriele Sacino; Riccardo Ravallese; Roberto Ravallese; Leonarda De Benedictis; Anna Morea; Roberta Iatta; Simone Giannecchini; Maria A. Stincarelli; Maria Chironna; Claudia Maria Trombetta; et al. (Viruses)
Background: West Nile virus (WNV) is a mosquito-borne RNA virus, with birds as reservoirs and humans as incidental hosts. WNV often causes asymptomatic infections, but severe neuroinvasive disease occurs in fewer than 1% of human cases. Recent climatic changes and occupational exposure have increased its spread, particularly in Southern Italy. This study aimed to assess WNV seroprevalence and occupational risks among outdoor workers to guide targeted public health interventions. Methods: This cross-sectional study was conducted in the Apulia region, southeastern Italy, from November 2023 to April 2024. Participants completed a detailed questionnaire on socio-demographics, occupational exposure, travel history, and health symptoms. Blood samples were analyzed using enzyme-linked immunosorbent assay (ELISA) and neutralization assays to detect WNV-specific antibodies. Results: 250 outdoor workers in southeastern Italy were recruited, including agricultural workers, veterinarians, forestry workers, and livestock breeders. The latter showed the highest WNV prevalence at 6.5%. Protective measures such as repellent use (β = −0.145, OR = 0.95, p = 0.019) and personal protective equipment (PPE) usage (β = −0.12, OR = 0.94, p = 0.04) significantly reduced the likelihood of WNV infection. Conclusions: The study highlights the significant occupational risk posed by WNV to outdoor workers involved in livestock breeding in Southern Italy, likely due to their frequent exposure to mosquito-prone environments. Tailored public health strategies and education programs are needed to protect high-risk outdoor workers from WNV, amidst the backdrop of changing climatic conditions that favor increased transmission.